HUBUNGAN ANTARA AKTIVITAS DAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR IPS TERPADU - Theresia Wisatantri Nainggolan; Raden Gunawan Sudarmanto; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2013)
This research aim to know relationship between the activity and the dicipline of learning to result learn student Social Integrated. Method the used is descriptive research of verifikatif with approach of ex post facto and of survey. The result  of research for use. (1) There is a positive relationship between learning activities with result learn student Social Integrated Odd Semester Grade VII Xaverius 4 junior Bandar Lampung Academic Year 2012/2013, (2) There is a positive relationship between learning discipline with result learn student Social Integrated Odd Semester Grade VII Xaverius 4 junior Bandar Lampung Academic Year 2012/2013, (3) There is a positive relationship between learning activities and learning discipline with result learn student Social Integrated Odd Semester Grade VII Xaverius 4 junior Bandar Lampung Academic Year 2012/2013. Keywords: learning activities, learning discipline, result learn